(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
In India, sports have never been a main stream issue for policy makers. Sports have received the attention mostly as a source of entertainment in Indian social space. Even the approach of the common man in India towards the sports traditionally has been casual and emotional rather than rational. In other words, the sports and related issues have always occupied a secondary place in Indian socio-political-legal sphere. It is well known fact that baring few sports, India has not been doing very good in the realm of the sports. This approach of the Indian society towards sports has been main cause for its underperformance at the global level in the field of sports. The reason for the underperformance is not only rooted in human resources but certainly an issue and structure of sports governance in India. The vacuum in the sphere of sports governance need to be addressed urgently on priority basis to come out of present state of inertia. The researchers through this paper intend to examine the present status of sports law in India and suggest future roadmap for the sports governance as well.